Learning within a social movement: The Chicago African-American experience. - Phyllis Cunningham; Regina Curry (Adult Education Research Conference, 1997)
A study of the Empowerment Zone in which over one thousand poor residents mobilized to learn, create knowledge, and formulate a plan to reinvent government and alleviate poverty.